Metagenome-based characterization of the gut bacteriome, mycobiome, and virome in patients with chronic hepatitis B-related liver fibrosis - Chen, Wenlin; Liang, Fang; Zhang, Yue; Zhang, Yuncheng; Lv, Jinzhen; Jin, Xiande; Ran, Yun; Li, Shenghui; Sun, Wen (Frontiers in Microbiology, 2024)
The gut microbiota is believed to be directly involved in the etiology and development of chronic liver diseases. However, the holistic characterization of the gut bacteriome, mycobiome, and virome in patients with chronic hepatitis B-related liver fibrosis (CHB-LF) remains unclear. In this study, we analyzed the multikingdom gut microbiome (i.e., bacteriome, mycobiome, and virome) of 25 CHB-LF patients and 28 healthy individuals through whole-metagenome shotgun sequencing of their stool samples. We found that the gut bacteriome, mycobiome, and virome of CHB-LF patients were fundamentally altered, characterized by a panel of 110 differentially abundant bacterial species, 16 differential fungal species, and 110 differential viruses. The representative CHB-LF-enriched bacteria included members of Blautia_A (e.g., B. wexlerae, B. massiliensis, and B. obeum), Dorea (e.g., D. longicatena and D. formicigenerans), Streptococcus, Erysipelatoclostridium, while some species of Bacteroides (e.g., B. finegoldii and B. thetaiotaomicron), Faecalibacterium (mainly F. prausnitzii), and Bacteroides_A (e.g., B. plebeius_A and B. coprophilus) were depleted in patients. Fungi such as Malassezia spp. (e.g., M. japonica and M. sympodialis), Candida spp. (e.g., C. parapsilosis), and Mucor circinelloides were more abundant in CHB-LF patients, while Mucor irregularis, Phialophora verrucosa, Hortaea werneckii, and Aspergillus fumigatus were decreases. The CHB-LF-enriched viruses contained 18 Siphoviridae, 12 Myoviridae, and 1 Podoviridae viruses, while the control-enriched viruses included 16 Siphoviridae, 9 Myoviridae, 2 Quimbyviridae, and 1 Podoviridae_crAss-like members.Moreover, we revealed that the CHB-LF-associated gut multi-kingdom signatures were tightly interconnected, suggesting that they may act together on the disease. Finally, we showed that the microbial signatures were effective in discriminating the patients from healthy controls, suggesting the potential of gut microbiota in the prediction of CHB-LF and related diseases. In conclusion, our findings delineated the fecal bacteriome, mycobiome, and virome landscapes of the CHB-LF microbiota and provided biomarkers that will aid in future mechanistic and clinical intervention studies.